Cash Wakf Implementation Viewed From Bi Al-Urfi Ijtihad Methodology - Nurul Inayah (Journal Research of Economic and Bussiness, 2023)
This study aims to implement cash waqf in terms of the Istihsan Bi Al-Urfi ijtihad methodology. This is related to the phenomenon that there are still those who doubt the permissibility of cash waqf (cash waqf). The research method used is qualitative analysis. The data collection technique used in this paper is literature study and observation. The technical analysis of the data used is by using a qualitative analysis approach, namely by explaining various arguments regarding the law of cash waqf from various ijtihad methodologies of fiqh scholars. From the results of the research conducted, the authors conclude that the Hanafi School also allows waqf as a conclusion, on the basis of what has been done (custom), many people have done. The way of doing cash waqf according to the Hanafi school is the modality of the mudharabah method while the profits are donated to the waqf. According to al Bakri, the Shafi'i school does not allow cash waqf, because dinars and dirhams (money) will be discontinued. However, some followers of the Shafi'i school allow cash waqf. And the opinion of scholars regarding the object of waqf explains that the conditions for waqf objects (must be objects, useful, not disposable, not unlawful in substance and must belong to the wakif perfectly).